PENGARUH BEBAN KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN DI PT. WANDA JAYA PROPERTY (LINDA REGENCY) DI MABUUN KABUPATEN TABALONG, KALIMANTAN SELATAN (JAPB, 2022)
Demands of tasks given to employees to work on which must be completed within a predetermined time. While work effectiveness is the success of an employee who is able to carry out and complete the tasks assigned by an organization or group in a timely manner, so that the agreed goals are achieved within a company or organization. The purpose of this study was to determine the effect of workload on the effectiveness of employee performance at PT. Wanda Jaya Property (Linda Regency) in Mabuun, Tabalong Regency, South Kalimantan. The research method used in this study is a quantitative method. The population in this study amounted to 80 people. Because the author uses a saturated sample, the sample is taken from the entire population. The analysis tool uses the Statistical Package for Social Science (SPSS) program. The amount of influence is 69.7% and 31% is influenced by other factors outside of this study. Keywords: Workload, Work Effectiveness, Property.